2014
DOI: 10.1167/iovs.14-14029
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Race-Related Differences in Human Scleral Material Properties

Abstract: The age- and race-related differences in scleral material properties result in a loss of scleral compliance due to a higher shear stiffness and a lower level of stretch at which the collagen fibrils uncrimp. The loss of compliance should lead to larger high frequency IOP fluctuations and changes in the optic nerve head (ONH) biomechanical response in the elderly and in persons of African ancestry, and may contribute to the higher susceptibility to glaucoma in these at-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 67 publications
3
98
2
Order By: Relevance
“…Other recent scleral mechanics studies have uti lized laser speckle interferometer (ESPI) to measure surface dis placement [17,24,25,51]. ESPI was shown to have an unmatched 16nm accuracy in displacement calculation [63], Using ESPI, Girard et al [17] in monkeys and Fazio et al [24] in humans detected an age-related stiffening of scleral tissue, which is con sistent with what we observed using DIC [18], A similar inverse finite element optimization method was applied to match ESPImeasured displacement fields obtained in an inflation test to model-predicted displacement fields and calculate the anisotropic hyperelastic material properties of the monkey [17,51] and human [22,52] sclera. Although ESPI has a noticeably better displace ment resolution than DIC, the quality of the fit in our study is comparable to if not improved over those studies.…”
Section: Adjustmentsupporting
confidence: 74%
See 1 more Smart Citation
“…Other recent scleral mechanics studies have uti lized laser speckle interferometer (ESPI) to measure surface dis placement [17,24,25,51]. ESPI was shown to have an unmatched 16nm accuracy in displacement calculation [63], Using ESPI, Girard et al [17] in monkeys and Fazio et al [24] in humans detected an age-related stiffening of scleral tissue, which is con sistent with what we observed using DIC [18], A similar inverse finite element optimization method was applied to match ESPImeasured displacement fields obtained in an inflation test to model-predicted displacement fields and calculate the anisotropic hyperelastic material properties of the monkey [17,51] and human [22,52] sclera. Although ESPI has a noticeably better displace ment resolution than DIC, the quality of the fit in our study is comparable to if not improved over those studies.…”
Section: Adjustmentsupporting
confidence: 74%
“…Age-related accu mulation of nonenzymatic cross-links has been reported in various tissues [20] and has commonly been associated with a stiffening of the tissue. Increased mechanical stiffness was measured in the aging human [18,21,22], monkey [17], and mouse [23] sclera. More recently, Fazio et al [24,25] showed that the strains in the peripapillary sclera were significantly lower in older human speci mens.…”
Section: Introductionmentioning
confidence: 99%
“…Raising the steady-state IOP effectively increased the stiffness of the entire corneoscleral shell, whereas chemical crosslinking treatment only alters a small region. This suggests that ubiquitous alterations in corneoscleral stiffness due to aging (Coudrillier et al, 2015; Coudrillier et al, 2012; Fazio et al, 2014) or race/genetics (Grytz et al, 2014) could have a much stronger impact on IOP spikes and glaucoma risk than localized treatment such as corneal or scleral crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…ONH connective tissues stiffen with age (Fazio et al, 2014a; Fazio et al, 2014b; Grytz et al, 2014), although it is not clear if the individual components of those tissues stiffen at different rates. The process may not progress at comparable rates in all humans, as there is strong evidence that it is influenced by genetic factors (Fazio et al, 2014b).…”
Section: Questions Related To Onh Structure and Glaucoma Susceptibmentioning
confidence: 99%